The Place of the Evil Eye in Religious and Mythological Literature - Guliyev, Ibrahim (Scholarya Demo Journal of Ruby, 2021)
The existence of the evil eye is undeniable. It is mentioned in the Qur’an, and hadiths attest to its veracity. In addition to all of this, there are numerous legends, proverbs, and poems about this subject in mythology, philosophy, folklore, and literature from all over the world, including our own. Its true nature, however, has yet to be scientifically proven. Although modem scientific research by psychologists and parapsychologists has only partially confirmed the existence of the evil eye, it has also concluded that the presence of negative energy in some people is released from the human body through the eyes. As a result, it appears in mankind’s mythological thought, as well as our folklore and customs, in addition to religious origins, and it must be investigated. Given this, numerous sources, including the works of Tafsir and Hadith experts on the subject, were consulted, and the subject was thus researched from the standpoint of Tafsir studies. Anti-aliasing has been demonstrated through research. As a result, some people’s claims about the absence of the evil eye or its superstitions are neither scientific nor religious in nature. It is also a mistake to believe such people because they cannot provide solid evidence that this phenomenon does not exist. As the title suggests, the focus of the study is the presence of the evil eye and its place in religious and mythical sources. Furthermore, given the importance of researching the issue through the lens of literature and folklore, we have included the ideas expressed in classical poets’ poems and proverbs.